Mapping quantitative trait loci associated with starch paste viscosity attributes by using double haploid populations of rice (Oryza sativa L.) - Tahmina SHAR; Zhong-hua SHENG; Umed ALI; Sajid FIAZ; Xiang-jin WEI; Li-hong XIE; Gui-ai JIAO; Fahad ALI; Gao-neng SHAO; Shi-kai HU; Pei-song HU; Shao-qing TANG (Journal of Integrative Agriculture, 2020)
The paste viscosity attributes of starch, measured by rapid visco analyzer (RVA), are important factors for the evaluation of the cooking and eating qualities of rice in breeding programs. To determine the genetic roots of the paste viscosity attributes of rice grains, quantitative trait loci (QTLs) associated with the paste viscosity attributes were mapped, using a double haploid (DH) population derived from Zhongjiazao 17 (YK17), a super rice variety, crossed with D50, a tropic japonica variety. Fifty-four QTLs, for seven parameters of the RVA profiles, were identified in three planting seasons. The 54 QTLs were located on all of the 12 chromosomes, with a single QTL explaining 5.99 to 47.11% of phenotypic variation. From the QTLs identified, four were repeatedly detected under three environmental conditions and the other four QTLs were repeated under two environments. Most of the QTLs detected for peak viscosity (PKV), trough viscosity (TV), cool paste viscosity (CPV), breakdown viscosity (BDV), setback viscosity (SBV), and peak time (PeT) were located in the interval of RM6775–RM3805 under all three environmental conditions, with the exception of pasting temperature (PaT). For digenic interactions, eight QTLs with six traits were identified for additive×environment interactions in all three planting environments. The epistatic interactions were estimated only for PKV, SBV and PaT. The present study will facilitate further understanding of the genetic architecture of eating and cooking quality (ECQ) in the rice quality improvement program.